The Isoform Selective Roles of PI3Ks in Dendritic Cell Biology and Function - Aksoy, Ezra; Saveanu, Loredana; Manoury, Bénédicte (Frontiers in Immunology, 2018)
Phosphoinositide -3 kinases (PI3Ks) generate 3-phosphorylated phosphoinositide lipids that are implicated in many biological processes in homeostatic states and pathologies such as cancer, inflammation and autoimmunity. Eight isoforms of PI3K exist in mammals and among them the class I PI3K, p110γ and PI3Kδ, and class III Vps34 being the most expressed and well characterised in immune cells. Following engagement of pathogen recognition receptors (PRRs), PI3Ks coordinate vital cellular processes of signalling and vesicular trafficking in innate phagocytes such as macrophages and professional antigen presenting dendritic cells (DCs). Although previous studies demonstrated the involvement of PI3K isoforms in innate and adaptive immune cell types, the role of PI3Ks with respect to DC biology has been enigmatic. Thus, this review, based on studies involving PI3K isoforms, highlight how the different PI3Ks isoforms could regulate DC functions such as antigen processing and presentation including PRR responses.